What’s in the Pipeline? Evidence on the Transmission of SARS-CoV-2 via Building Wastewater Plumbing Systems - Dight, Thomas; Gormley, Michael (Frontiers in Built Environment, 2021)
There is emerging evidence of the transmission of SARS-CoV-2 via the sanitary plumbing wastewater system, a known transmission pathway of SARS-CoV-1. These events can no longer be dismissed as isolated cases, yet a lack of awareness and of basic research makes it impossible to say just how widespread this mode of transmission might be. Virus is transmitted within wastewater systems by the aerosolisation of wastewater and subsequent transport of bioaerosols on naturally occurring airflows within the piped network. Central to the debate around risk to building occupants from SARS-CoV-2 spread via wastewater plumbing systems is the question of infectivity of faeces, urine and associated aerosols. This paper presents an examination of the processes which underlie this mode of transmission, and the existing epidemiological evidence, as well as existing mitigation strategies; significant gaps in the state of the knowledge are also identified. It is hoped that this review will cultivate a wider awareness and understanding of this most overlooked of threats, and to facilitate the selection and adoption of appropriate mitigation strategies. Key gaps in the knowledge span the rate of generation of bioaerosols within the building drainage system, their composition and transport properties, and the viability and infectivity of virions and other pathogens which they carry. While much of this work will be conducted in the laboratory, we also identify a dearth of field observations, without which it is impossible to truly grasp the scale of this problem, its character, or its solution.